The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.dnarep.2007.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of in vivo interactions between Rev1 protein and other Y-family DNA polymerases in animals and yeasts

Abstract: SummaryEukaryotes are endowed with multiple specialized DNA polymerases, some (if not all) of which are believed to play important roles in the tolerance of base damage during DNA replication. Among these DNA polymerases, Rev1 protein (a deoxycytidyl transferase) from vertebrates interacts with several other specialized polymerases via a highly conserved C-terminal region. The present studies assessed whether these interactions are retained in more experimentally tractable model systems, including yeasts, flie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…The final crystallization sample containing the quaternary complex of the Rev1 CTD, Rev3/7, and Pol RIR complex was prepared by passing the protein mixture of Rev3/7 with a slight molar excess amount of the Rev1 CTD-Pol RIR complex through a size exclusion column ( 15 N-labeled Rev1 CTD in the presence of equal molar ratios of both GB1-Pol RIR and Pol was also recorded to establish the formation of the quaternary Rev1 CTD-Rev3/ 7-Pol RIR complex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final crystallization sample containing the quaternary complex of the Rev1 CTD, Rev3/7, and Pol RIR complex was prepared by passing the protein mixture of Rev3/7 with a slight molar excess amount of the Rev1 CTD-Pol RIR complex through a size exclusion column ( 15 N-labeled Rev1 CTD in the presence of equal molar ratios of both GB1-Pol RIR and Pol was also recorded to establish the formation of the quaternary Rev1 CTD-Rev3/ 7-Pol RIR complex.…”
Section: Methodsmentioning
confidence: 99%
“…Rev1 interaction is required for the protective role of Pol against benzo[a]pyrene in mammalian cells, and it promotes Pol -mediated suppression of spontaneous mutations in human cells (17,18). Although the interactions between the Rev1 CTD and the RIRs of Y-family polymerases , , and are only found in vertebrates (15), the Rev1 CTD-Pol interaction is evolutionarily conserved from yeast to humans, highlighting the essential role of the Rev1-Pol interaction in translesion synthesis. Consistent with this notion, the Rev1 CTD is required for effective DNA damage tolerance in mammalian cells, and mutations of the Rev1 CTD display a profound defect in translesion synthesis with significantly reduced damage-induced mutagenesis in yeast (11,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutants in the UBM2 of Rev1 also display decreased survival and mutagenesis in response to DNA damage that is likely caused by a less efficient interaction with monoubiquitinated PCNA (Guo et al 2006b;Wood et al 2007;D'Souza et al 2008;Bomar et al 2010). Additional studies found that the last $100 amino acids of Rev1 could interact with the other TLS polymerases in mammalian cells (Murakumo et al 2001;Guo et al 2003;Ohashi et al 2004;Tissier et al 2004) and in S. cerevisiae (Acharya et al 2005(Acharya et al , 2006D'Souza and Walker 2006;D'Souza et al 2008;Kosarek et al 2008). Not surprisingly, truncations of, or point mutations in, the C terminus cause severe survival and mutagenesis defects after DNA damage (Larimer et al 1989;Ross et al 2005;Acharya et al 2006;D'Souza et al 2008;Kosarek et al 2008).…”
mentioning
confidence: 99%
“…Additional studies found that the last $100 amino acids of Rev1 could interact with the other TLS polymerases in mammalian cells (Murakumo et al 2001;Guo et al 2003;Ohashi et al 2004;Tissier et al 2004) and in S. cerevisiae (Acharya et al 2005(Acharya et al , 2006D'Souza and Walker 2006;D'Souza et al 2008;Kosarek et al 2008). Not surprisingly, truncations of, or point mutations in, the C terminus cause severe survival and mutagenesis defects after DNA damage (Larimer et al 1989;Ross et al 2005;Acharya et al 2006;D'Souza et al 2008;Kosarek et al 2008). Given that these domains bind other proteins and contribute to survival and mutagenesis for a spectrum of DNA damage, it has been proposed that Rev1 acts a scaffolding protein that promotes the recruitment of TLS polymerases to sites of DNA adducts and/or aids in the recognition of DNA lesions (Waters et al 2009).…”
mentioning
confidence: 99%